The Application of Augmented Reality for Economic Crop Cultivation: A Case Study of the Muang Kan Pattana Municipality, Mae Taeng District, Chiang Mai Province - Petagon, Roselin; Suwanakul, Panuwat; Pantho, Oranuch (Community and Social Development Journal, 2021)
The research objective were 1) to develop an augmented reality application for Economic crop cultivation and 2) to study a system users satisfaction. All five experts used to evaluate the effectiveness were obtained by a specific selection method. 30 general users were randomly selected as the sample group used in the satisfaction study. The research tools consisted of the augmented reality application for crop cultivation, the performance evaluation of application and the satisfaction questionnaire divided into 3 parts: the content integrity design formatting, presentation of information and benefits for the implementation of AR technology. The statistics used in this research were mean, and standard deviation. The results of this research showed that the highest efficacy and satisfaction assessment values of the experts and the samples was part of the usefulness of AR technology, the mean was 4.76, the standard deviation of 0.42 and the mean was 4.45, the standard deviation 0.57, respectively.